Antidepressant Effect of Paeoniflorin Is Through Inhibiting Pyroptosis CASP-11/GSDMD Pathway - Tian, Dan-Dan; Wang, Min; Liu, An; Gao, Mei-Rong; Qiu, Chen; Yu, Wen; Wang, Wen-Ju; Zhang, Kun; Yang, Le; Jia, Yan-Yan; Yang, Chang-Bin; Wu, Yu-Mei (Molecular neurobiology, 2021)
Nod-like receptor protein 3 (NLRP3)-associated neuroinflammation mediated by activated microglia is involved in the pathogenesis of depression. The role of the pore-forming protein gasdermin D (GSDMD), a newly identified pyroptosis executioner downstream of NLRP3 inflammasome mediating inflammatory programmed cell death, in depression has not been well defined. Here, we provide evidence that paeoniflorin (PF), a monoterpene glycoside compound derived from Paeonia lactiflora , ameliorated reserpine-induced mouse depression-like behaviors, characterized as increased mobility time in tail suspension test and forced swimming test, as well as the abnormal alteration of synaptic plasticity in the depressive hippocampus. The molecular docking simulation predicted that PF would interact with C-terminus of GSDMD. We further demonstrated that PF administration inhibited the enhanced expression of GSDMD which mainly distributed in microglia, along with the proteins involved in pyroptosis signaling transduction including caspase (CASP)-11, CASP-1, NLRP3, and interleukin (IL)-1β in the hippocampus of mice treated with reserpine. And also, PF prevented lipopolysaccharide (LPS) and adenosine triphosphate (ATP)-induced pyroptosis in murine N9 microglia in vitro, evidenced by inhibiting the expression of CASP-11, NLRP3, CASP-1 cleavage, as well as IL-1β. Furthermore, VX-765, an effective and selective inhibitor for CASP-1 activation, reduced the expression of inflammasome and pyroptosis-associated proteins in over-activated N9 and also facilitated PF-mediated inhibition of pyroptosis synergistically. Collectively, the data indicated that PF exerted antidepressant effects, alleviating neuroinflammation through inhibiting CASP-11-dependent pyroptosis signaling transduction induced by over-activated microglia in the hippocampus of mice treated with reserpine. Thus, GSDMD-mediated pyroptosis in activated microglia is a previously unrecognized inflammatory mechanism of depression and represents a unique therapeutic opportunity for mitigating depression given PF administration.